PENGGUNAAN MODEL OPEN ENDED LEARNING DENGAN MULTIMEDIA UNTUK MENINGKATKAN PEMBELAJARAN BANGUN RUANG SISWA KELAS V SD NEGERI 3 PANJER TAHUN AJARAN 2015/2016 - TASIRAH, TASIRAH (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Open Ended Learning Model Using Multimedia in Improving Learning about Geometry for the Fifth Grade Students of SD Negeri 3 Panjer in the Academic Year of 2015/2016. The objectives of this research are to improve Mathematics learning about geometry. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were fifth grade students of SD Negeri 3 Panjer in the academic year of 2015/2016 totaling 15 students. Techniques of collecting data were observation, interview, documentation, and test. The result of this research showed that the use Open Ended Learning model using multimedia through appropriate steps could improve Mathematics learning about geometry for the fifth grade students of SD Negeri 3 Panjer in the academic year of 2015/2016 Keywords: Open Ended Learning, multimedia, Mathematics Abstrak: Penggunaan Model Open Ended Learning dengan Multimedia untuk Meningkatkan Pembelajaran Bangun Ruang Siswa Kelas V SD Negeri 3 Panjer Tahun Ajaran 2015/2016. Tujuan penelitian untuk meningkatkan pembelajaran Matematika tentang bangun ruang. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) kolaboratif selama 3 siklus, tiap siklus terdiri dari tahap perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitian adalah siswa kelas V SD Negeri 3 Panjer sejumlah 15 siswa. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, dokumentasi dan tes. Hasil penelitian menunjukkan bahwa penggunaan model Open Ended Learning dengan multimedia dapat meningkatkan pembelajaran bangun ruang siswa kelas V SD Negeri 3 Panjer tahun ajaran 2015/2016. Kata Kunci: Open Ended Learning, multimedia, Matematika